Revealing PTSD Symptoms Experienced by Kat Baker Using Internal Conflicts in “Spinning Out” TV Series - Putu Agnatya Mahadi Putri; I Nyoman Aryawibawa; I Nengah Sudipa (Udayana University, 2023)
This article presents a qualitative psychoanalysis study on the main character named Kat baker in TV Series titled